ナンキョク プリンスオラフ カイガン シンナンガン ロガン チタイ ノ ケイソウ - 福島, 博; フクシマ, ヒロシ; FUKUSHIMA, Hiroshi (国立極地研究所, 1962)
P(論文) The author investigated the flora, particularly on algae, of the Shin-nan Rock Ice-free Area, on the Prince Olav Coast in the Antarctic Continent, on Feb. 10, 1961. As a result of microscopic observations of the samples in 28 bottles which were collected from four ponds, 34 diatoms have been identified. The environmental factors and the number of species at each station are as follows: The most common character of diatoms in each pond is that the number of individuals of each species is few. More species are found adhering to stones on the bottom of ponds than in the sands on the bottom. In one of the pond, St. 4, several individuals of four peragic species, namely, Coscinodiscus sp., Fragilariopsis antarctica, Fragilariopsis cylindrus, Fragilariopsis obliquecostata, which are common in the adjacent sea, are found, but in other ponds the number of individuals is not so large. This is probably ascribed to the fact that St. 4 is located nearer to the sea and lower above the sea level than other stations. Peragic diatoms have been often found in the ponds and lakes of the Antarctic regions (CARLSON, 1912, NEGORO, 1961) and also in the ponds of the Shin-nan Rock Ice-free Area. Hantzschia amphioxys and Diploneis sp. are found in each of the 28 samples, an Nitzschia palea is common in three samples. In Syowa Base and in the Antarctic ragions, Hantzschia amphioxys and Navicula muticopsis are abundant, often becoming dominant species, but are very few in the Shin-nan Rock Ice-free Area. In conclusion, diatom vegetation in the Shin-nan Rock Ice-free Area appears to be different from that in the neighbourhood of Syowa Base. Among the 34 species of diatoms which are found in this area, only the following four are endemic species, Fragilariopsis antarctica, Fragilariopsis obliquecostata, Navicula muticopsis, Tropidoneis laevissima, while others are common species. departmental bulletin paper